A mechanoelectrical mechanism for detection of sound envelopes in the hearing organ - Alfred L. Nuttall (Nature Portfolio, 2018)
The sound envelope is important for speech perception. Here, the authors look at mechanisms by which the sound envelope is encoded, finding that it arises from distortion produced by mechanoelectrical transduction channels. Surprisingly, the envelope is not present in basilar membrane vibrations.